<span>Simplifying
7 + -2(2 + 3x) = 27
7 + (2 * -2 + 3x * -2) = 27
7 + (-4 + -6x) = 27
Combine like terms: 7 + -4 = 3
3 + -6x = 27
Solving
3 + -6x = 27
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3' to each side of the equation.
3 + -3 + -6x = 27 + -3
Combine like terms: 3 + -3 = 0
0 + -6x = 27 + -3
-6x = 27 + -3
Combine like terms: 27 + -3 = 24
-6x = 24
Divide each side by '-6'.
x = -4
Simplifying
x = -4</span>
You can say 4? Because the greatest common factor of 12 and 20 is 4
Answer:
1.85
Step-by-step explanation:
1.75-0.5+0.6= 1.85 or 1 17/20